River Flood Modelling For Flooding Risk Mitigation in Iraq - Mohammad Esam Shareef; Dheyaa Ghanim Abdulrazzaq (Salehan Institute of Higher Education, 2021)
River flood events have recently been increased due to many reasons such as climate change and excessive land usage. Thus, one of the greatest challenges is to control the flooding in urban areas. River flooding has become a phenomenon worldwide in general and in Iraq specifically. This is associated with the rapid increase of urbanization as well as mismanagement of land utilization; especially those located near the river banks, in addition to lack of consideration in terms of the design and implementation of drainage networks. In Iraq and especially in Al-Anbar governorate, studies in the field of flood simulation control have been rare. This study aims to suggest a fast and accurate methodology for local authorities, by providing a proposed solution and prediction of flooding area in the case study of the Fallujah barrage. Global Mapper software has been used to produce simulation photos on flooding area. Earth Explorer USGS website has been used to download water body data; and Global Digital Surface website has been used to extract and download the surface elevation data. The result of the simulation photos has predicted valuable information about the flooding area and proposed a general vision on the areas that are under threat of flooding. Four main areas were exposed to flooding, area 1, area 2, area 3, and area 4; A total flooding area of 11.89 km2. The total maximum operational level for the barrage was designed to be 44.79 m above sea level. Also, the recommended maximum operation level for the barrage was 43 m ASL. Doi: 10.28991/cej-2021-03091754 Full Text: PDF